Pandemic Covid-19 Resilience In Improving Coffee Business Marketing in Local Coffee Bali as Tourism Product - Suarjaya, I Nyoman; Wisnawa, I Made Bayu (Journal of Business on Hospitality and Tourism, 2022)
The Covid-19 virus is increasingly spreading in Indonesia, several policies set by the Government in Indonesia have had an impact on several sectors in Indonesia, one of which is the economic sector. This study aims to analyze the internal and external factors that affect Local Coffee Bali as tourism product and marketing strategies that can be applied by the management of Local Coffee Bali after facing the Covid-19 pandemic. The research methodology used is descriptive qualitative to analyze data by the influence of the business environment both internally and externally. The results of this study indicate that from the analysis of the internal environment using the SW matrix, the most influential strength (Strengths) is product quality and the most influential weakness (Weaknesses) factor is increasing promotional activities. While the external environment results through the OT matrix, the most influential opportunities are adding product variant innovations and the most influential Threats is increasing a comfortable and shady dine-in place. While the results of the SWOT matrix analysis through four alternative strategies can be found marketing strategies that can be applied by the management of Local Coffee Bali after facing the Covid-19 pandemic for tourism products are adding product variant innovations, improving product quality according to market prices, increasing promotional activities, increasing places to shop, cozy and shady dine-in.